Assessment, Research and Use of Methods for Determining the Strength of Base Courses of Road Pavement Structure - Bertulienė, Lina (The Baltic Journal of Road and Bridge Engineering, 2012)
This summary of the author’s PhD thesis supervised by Prof Dr Alfredas Laurinavičius and defended on 21 December 2011 at the Vilnius Gediminas Technical University. The thesis is written in Lithuanian and is available from the author upon request. Chapter 1 covers the analysis of the literatute. There is the review of research works carried out in Europe and other countries of the world for determining structural strength of road pavements by calculation methods during their design and gives a wide description of the main methods used in Lithuania. Chapter 2 gives the analysis of the effect of different factors on the road pavement strength, studies a damaging impact of the axle loads of moving vehicles on road pavement, also the dependency of strength and condition of road pavement on the changes in the ambient temperature and seasonal precipitation. Chapter 3 analyses the stages of experimental research, selection of a test section for experimental research, methodology for investigating pavement structure parameters and the equipment used, gives the analysis of research data obtained by the author. Chapter 4 describes statistical analysis and assessment of research results obtained on the subgrade and the lower pavement layers. Reduction coefficients are suggested to be used betwen the static and dynamic measuring methods.